Caracterização, condições de metamorfismo e implicações geotectônicas dos migmatitos granatíferos da Serra Do Caparaó (MG) - Pedro Leonardo Nicolau do Carmo Rossi Vieira (2018)
Ultrahigh temperature (UHT) metamorphic rocks outcrops on the Caparao Range (southeastern Brazil) as tectonic slices of orthogneisses and migmatites from basement units of the Araçuai Orogen alongside metasedimentary migmatites. These garnet-bearing migmatites are observed as tectonic intercalations into orthoderived units, and can be subdivided into hercynite-sillimanite-garnet migmatites and orthopyroxene-garnet-biotite migmatites. In this work, we conducted petrological studies on these garnet-bearing rocks in order to better comprehend the metamorphic conditions attained by the lowermost parts of the Araçuai Orogen. Hercynite-sillimanite-garnet migmatites show preserved metamorphic peak assemblages containing stable sapphirine+quartz and hercynite+quartz, diagnostic of ultrahigh temperature (UHT) metamorphic terrains worldwide. Orthopyroxene-garnetbiotite migmatites exhibit high-Al orthopyroxene crystals, also characteristic of rocks submitted to UHT conditions. Combining Average P-T (THERMOCALC) thermobarometry with phase-equilibria modelling, metamorphic peak P-T conditions of 1066-1076 °C, 7.6-7.9 kbar are obtained for hercynite-sillimanite-garnet migmatites and 988-1023 °C, 9.8-10.9 kbar for orthopyroxene-garnetbiotite migmatites, the highest calculated for Araçuai Orogen rocks. U-Pb LA-ICP-MS geochronology data obtained from zircon crystals from both migmatite types provided minimum metamorphic ages between 626-585 Ma, considerably older than the metamorphic peak ages obtained from other granulite-facies metasedimentary sequences outcropped in the crystalline nuclei of the orogen. The possible sources of heat for achieving UHT metamorphism may be geodynamically related to subduction, associated to magma underplating during arc related magmatism or to partial assimilation of the slab during tectonic exhumation. This newfound occurrence of UHT metamorphic rocks sums up to the yet few worldwide occurrences of this kind of terrain.